2002
DOI: 10.1002/jqs.711
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary record of a tsunami during Roman times, Bay of Cadiz, Spain

Abstract: Historical data show that the Gulf of Cadiz has been exposed to destructive tsunamis during at least the past 2000 yr. The last tsunami was generated by the AD 1755 Lisbon earthquake, which affected the Atlantic coasts of Spain, Portugal and Morocco. Today, these littoral areas are intensely populated and the expected damage could be much greater. Tsunami studies are of great importance in helping to determine the recurrence interval of these events.The presence of washover fan deposits on the inland margin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 46 publications
(54 reference statements)
0
40
0
6
Order By: Relevance
“…3.6 The 2.2-2.3 kyr BP paleotsunami A high energy event 2200-2300 yr BP was positively identified by Luque et al (2002) on the Valedelagrana Spit Bar (Bay of Cadiz, Spain), with the input of coarse sands into tidal marsh deposits, similar to the sedimentary signature of the 1755 event in the same place. Vizcaino et al (2006) found a similar result for a debris flow in the Marques de Pombal core, attributing it a radiocarbon age of 2293±35 yr BP.…”
Section: The 36 Kyr Bp Paleotsunamimentioning
confidence: 98%
“…3.6 The 2.2-2.3 kyr BP paleotsunami A high energy event 2200-2300 yr BP was positively identified by Luque et al (2002) on the Valedelagrana Spit Bar (Bay of Cadiz, Spain), with the input of coarse sands into tidal marsh deposits, similar to the sedimentary signature of the 1755 event in the same place. Vizcaino et al (2006) found a similar result for a debris flow in the Marques de Pombal core, attributing it a radiocarbon age of 2293±35 yr BP.…”
Section: The 36 Kyr Bp Paleotsunamimentioning
confidence: 98%
“…Cadiz coast have been noted in many places along shore, such as the key-points of Punta Umbria, Dofiana, and Valdelagrana (Lario et al, 1995(Lario et al, a, 2001b(Lario et al, , 2002Lario, 1996;Dabrio et al, 1999;Luque et al, 2002;Ruiz et al, 2004, 200Sb ;Caceres et al, 2006). Wide spread occurrence of EWE features along the coast (breaching of spit barriers, intruding sandy layers with marine bioclasts in the inner estuaries, chenier development, occurrence of washover fans) and other effects of regional extent, such as the reorganisation of the back barrier drainage patterns of estuaries (e.g.…”
Section: The Largest Record Of Ewe Deposits Recorded Along the Gulf Ofmentioning
confidence: 99%
“…It must be also considered that, although Galbis The well-documented 1755 Lisbon tsunami-earthquake is clearly associated with the E3-turbidite in the off-shore record (Gracia et al, 2010). This recent EWE has an abundant historical written record for more than 30 sites along the south-western Spanish shores, complemented by extensive analyses of its geological effects on the Gulf of Cadiz area (Campos, 1991;Dabrio et al, 1999;Martinez Solares, 2001;Luque et al, 2001Luque et al, , 2004Luque, 2002;Morales et al, 200S;Lario et al, 2010).…”
Section: The Largest Record Of Ewe Deposits Recorded Along the Gulf Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Posteriormente, varias publicaciones han evidenciado este evento en distintos lugares de la costa atlántica (Luque et al, 2001(Luque et al, , 2002Silva et al, 2015, entre otros), hasta que finalmente ha sido asimilado a un tsunami que se produjo a finales del siglo III a.C., posiblemente entre el 218 y 209 a.C. (Rodriguez-Vidal et al, 2011), coincidiendo con la Segunda Guerra Púnica. Silva et al (2015) proponen denominarlo como "Lacus Ligustinus Earthquake", utilizando para ello el nombre del antiguo lugar geográfico donde se han recogido la mayor parte de sus evidencias geológicas (Rodríguez-Vidal et al, 2011).…”
Section: Registro Arqueológico De Eventos Costeros E Implicaciones Huunclassified